Illusion vs. Disillusion: Chinese Viewers’ Articulation of “House of Cards” - Zhaoxi (Josie) Liu (Journalism and Media, 2021)
This study explores how Chinese viewers articulate the meaning of the Netflix series “House of Cards” through analyzing viewer comments posted on Sohu Video, which streamed the show in China. A qualitative textual analysis of the comments reveals that the Sohu viewers turned the commenting of the show into articulations of democracy and China’s political conditions. In their articulation, some endorsed American democracy as a superb political system, while others resented it as being dark and corrupt, similar to the one in China. Still other viewers made a connection between “Cards” with China’s lack of freedom of speech. These connections were made under certain social conditions, including China’s internet providing a space for political discourse, tensions among different social forces and conflicting meaning systems existing in today’s China, and Chinese people’s increasing consumption of foreign media content and assumptions. Analyzing a particular case of transnational communication, this study demonstrates how the audience can make meaning of a foreign media product by connecting with their own social context, and how such articulations can be plural and multifaceted.